ANALISIS PERBEDAAN VERBA DIALEK SIKKA NATAR DAN DIALEK TANA AI DALAM BAHASA SIKKA - Maria Olivia; Maria E. D. Lering; Rimasi; Antonius M. K. Naro (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this study aims at analysing the differences of verbs between the Sika and the Tana Ai dialects. This is a qualitative descriptive research to describe objectively and accurately. The subjects were 14 people of Sika Natar Hamlet in sika village and Pauklor Hamlet in Pruda village, 7 from each village respectively. The seven informants consist of 1 expert informant and 6 ordinary informants. Data were analyzed using the equivalent method. The results of data analysis based on the and interview and listening during the conversations between the researcher and the informants proved that there are pairs of different verbas with different phonemes in the initial, middle and final consonant sounds. Then, from the pair of consonants and vowels sounds, were also found.